'Many to one' mode of CSCL and further discussion. (1st January 2011) - Zhao, Xinglong; Cai, Su
This study is an experiment of a new instructional model in classroom of higher education. Quantitative research methodology is employed in this study. Data are collected from 22 college students in the school of educational technology of a university. Findings indicate that 'many to one' mode participated by two to three students sharing one computer has a positive effect on the quality of learning. This contributes to the improvement in instructional quality of the college. As a result of this study, this paper advocates for an emphasis on experience-based computer-supported cooperative learning (ECSCL) in F2F classroom to facilitate the reform in higher education.